The application of rapid prototyping in facial surgeries: a series of case studies - Lima, Fábio Silva; Araújo Alves Dultra, Fátima Karoline; Dultra, Joaquim Almeida; Castro Rocha, Vanessa Álvares; Oliveira Carneiro, Pedro Paulo; Pereira Santana, Daiana Cristina (Revista de Ciências Médicas e Biológicas, 2019)
Aim: the aim of this paper is to report on the applicability of biomodels obtained from computerized tomography (CT) images through the technique of stereolithography (SLA) and three-dimensional printing (3DP), in the clinical case reports of patients who underwent surgeries involving dentoskeletal deformity, oral pathology and oral and maxillofacial trauma. Methodology: clinical case 01 deals with fractures in the orbital and zygomatic arch region that required reconstruction and correction of diplopia, by means of CT images, using the technique of three-dimensional printing through SLA, generating a mirrored biomodel for surgical planning and the making of customized prosthesis. In clinical case 02, by means of CT images, a biomodel utilizing the 3DP technique showed the total area invaded by invasive ameloblastoma, making it possible to plan the osteotomy with maximum preservation of the adjacent tissue and prior modeling of the plate. In clinical case 03, rapid prototyping technology (RP) was used to make customized prosthesis for temporomandibular joint, with the goal of correcting a serious idiopathic pathology provoking the resorption of the right and left condyles. Discussion: complex cases require the team to have recourse to technology for the implementation of the procedures, in order to offer excellent quality treatment to the patient, in addition to facilitating surgical planning and permitting the construction of customized prostheses. Conclusion: the rapid prototyping for the acquisition of biomodels is an important auxiliary tool for the surgical team.